Official Development Assistance in Japan's Strategy in Central Asia - O. A. Dobrinskaya (Vestnik MGIMO-Universiteta)
The article analyzes the official development aid (ODA) as a tool for ensuring Japan’s interests in Central Asia. The author puts forward an idea that ODA reflects the complex nature of Japan’s foreign policy which is a combination of a strategies based on national interests, efforts at implementation of liberal values and seeking common Asian identity. The research starts from the brief overview of history of the ODA and then proceeds to the coverage of Japan’s ODA towards Central Asia to demonstrate how the evolution of Japan’s political priorities manifested itself in the country’s assistance policy. The author uses quantitative and qualitative analysis of ODA to Central Asia as well as content analysis of the key documents on diplomacy and ODA. The research then focuses on the main directions of assistance and studies how they relate to Japan’s foreign policy goals. Further attention is given to the role Japan plays in the region, by assessing her position among the main donors of Central Asia as well as the significance of its aid from the point of view of economic development of the region, ODA’s security role and Japan’s efforts at preserving the cultural heritage of the region. The author comes to the conclusion that realism-based objectives such as getting access to the natural resources of the region, securing its geopolitical stance in the heart of Eurasia and ensuring the support for Japan’s bid to the UN Security Council seat by five Central Asian states dominate Japan’s ODA policy. It is also influenced by external factors, such as US-Japan military alliance and Japan’s geopolitical rivalry with China. At the same time, much of Japan’s efforts are directed at liberal goals such as promoting democracy in the region with Japan being a role model for democratization, supporting modernization and market economy. Assisting economic development and helping settle security issues with an emphasis on human security projects demonstrate not only Japan’s desire to boost its positive image in the region but also enhance its international reputation and its vision of Central Asia as a ground for cooperation with other countries. The author comes to the conclusion that cultural ODA is directed at objects related to shared history, mainly at preservation of the Buddhist heritage which Japan sees as a foundation for common identity and which underlies its connections to the Silk Road.